Anchored Argo profiling float experiments in the southern Baltic Sea: Puck Bay and Hel Peninsula - Merchel, Małgorzata; Walczowski, Waldemar; Wieczorek, Piotr (Frontiers in Marine Science, 2025)
This article presents the results of three experiments conducted in 2022–2023 using an Argo autonomous profiling float anchored to the seabed with a thin line. The aim of the study was to prevent the float from drifting in order to perform measurements in a precisely defined location. The experiments were carried out in the Baltic Sea - in Puck Bay and the vicinity of the Hel Peninsula. Puck Bay, a shallow and sheltered body of water with a unique and sensitive ecosystem, provided an excellent location for testing the method under calm conditions. In contrast, the northern areas of the Hel Peninsula, exposed to strong currents and high waves, allowed for the evaluation of the method’s effectiveness in more dynamic conditions. The results of the experiments demonstrated that anchoring the Argo float is effective in shallow and sheltered waters with low wave activity and weak currents, such as Puck Bay. However, in the more challenging environment of the Hel Peninsula, the method proved to be less effective, indicating its limitations in harsher environmental conditions. Standard Argo floats, which are most often deployed in deeper parts of the Baltic Sea, provide limited data from shallow-water areas, particularly those near the coast and in enclosed waters such as lagoons and bays. The introduction of anchored Argo floats could complement the existing network of drifting floats, ensuring better coverage of shallow-water areas and improving the quality of marine environmental monitoring.